Microbeam X-Ray Investigation of the Structural Transition from Circularly Banded to Ringless Dendritic Assemblies in Poly(Butylene Adipate) Through Dilution with Poly(Ethylene Oxide) - Nagarajan, Selvaraj; Chang, Chia-I; Lin, I-Chuan; Chen, Yu-Syuan; Su, Chean-Cheng; Lee, Li-Ting; Woo, Eamor M. (Polymers, 2025)
In this study, growth mechanisms are proposed to understand how banded dendritic crystal aggregates in poly(1,4-butylene adipate) (PBA) transform into straight dendrites upon dilution with a large quantity of poly(ethylene oxide) (PEO) (25–90 wt.%). In growth packing, crystal plates are deformed in numerous ways, such as bending, scrolling, and twisting in self-assembly, into final aggregated morphologies of periodic bands or straight dendrites. Diluting PBA with a significant amount of PEO uncovers intricate periodic banded assemblies, facilitating better structural analysis. Both circularly banded and straight dendritic PBA aggregates have similar basic lamellar patterns. In straight dendritic PBA spherulites, crystal plates can twist from edge-on to flat-on, similar to those in ring-banded spherulites. Therefore, twists—whether continuous or discontinuous—are not limited to the conventional models proposed for classical periodic-banded spherulites. Thus, it would not be universally accurate to claim that the periodic circular bands observed in polymers or small-molecule compounds are caused by continuous lamellar helix twists. Straight dendrites, which do not exhibit optical bands, may also involve alternate crystal twists or scrolls during growth. Iridescence tests are used to compare the differences in crystal assemblies of straight dendrites vs. circularly banded PBA crystals.